Post-hemorrhoidectomy pain descriptors - Priscilla, Hortense; Evangelista, Renata Alessandra; Sousa, Fátima Aparecida Emm Faleiros (Revista latino-americana de enfermagem, 2005)
This study aimed at comparing scales of judgements on differences and verifying the stability and agreement of the estimation made by descriptors of post-operative pain as assessed by three different samples. Nineteen subjects who had been submitted to hemorrhoidectomy participated in the study. They were randomly divided into three groups (Group C, T and F), who received an intravenous administration of ketoprofen 100 mg, tenoxicam 40 mg or physiological serum 0.9% before the surgery. The task of each participant was to assign a score, from 1 to 7, to each descriptor of the pain felt in the first complaint after surgery. The descriptors attributed to post-operative pain were evaluated by the psychophysical method of category estimation. The obtained results were: the descriptors with higher scores for Group C were intense, unbearable and terrible; for Group T, intense, tremendous and unbearable and for Group F, unbearable, intense and terrible.